Trends In Iraqi Oil Revenues After 2003 Under The Effect Of World Oil Prices Fluctuation - الشمري, عبد الصمد سعدون; احمد, خضير عباس (Journal of Economics and Administrative Sciences, 2012)
Characterized Iraq, being one of the oldest countries where oil was discovered in the Middle East since 1927, and possess a vast oil reserves. In addition, the production and marketing of Iraqi oil continued since 1934 and until the present time. Over the past eight decades, the range of economic benefit of the financial Iraq’s oil resources varied according to the applicable forms of investments in the oil sector in Iraq.This research included a study of the subject according to several aspects of the structure included the introduction and three sections. First Section, reviewed the possibilities of Iraqi oil. The second section focused on the issue of fluctuating prices of Iraqi oil exports in world oil markets. While the third section dealt with the implications of fluctuating oil prices on the Iraqi economy. Finally, the research ends with the conclusions